Angels:An Endangered Species - Godwin,Malcolm (New York Simon & Schuster, 1990)
Provides a traditional examination of the lore, art, and research concerning angels from ancient times to the present.
Keywords: Angels -- Comparative studies. Angels. Angels -- Pictorial works